Orientações curriculares para o ensino de geometria: do período da Matemática Moderna ao momento atual - Ferreira, Rogério Carlos (2008)
The present research is aimed to study Curricular Proposals produced since the Modern Mathematic´s Movement until the current days and to analyze how some didactic book collections had incorporated these Proposals. The consulted official documents had been the Curricular Guides of the State of São Paulo (1975), the National Proposal Curricular for Mathematc´s teaching of the State of São Paulo (1992) and Curricular Parameters for the Mathematics (1998), referring to the segment of the corresponding degree to current 6º. 9º. Year of Ensino Fundamental . The studied didactic collections had been: Matemática Curso Moderno , by Osvaldo Sangiorgi (1968 and 1971), A Conquista da Matemática , by Giovanni, Castrucci and Giovanni Jr (1992), and Matemática para Todos , by Luiz Marcio Imenes and Marcelo Lellis (2002). For the analysis of these documents and didactic books we take for base the theories of Roger Chartier (1991), which studies the different existing relations between the reading of the official legislation and the interpretation made by users. The analysis of didactic books had as focus the content of Geometry, and we support them in the studies of Josep Gascón (2001 and 2003) where the author argues interferences of episteologics and didactic models in the management of the Geometry´s lessons. In our analysis, we in such a way observe the interference of the Euclidianist model in the Curricular Guides as in the Matemática Curso Moderno , of the Almost-empiric model in the Proposal Curricular and the collection A Conquista da Matemática and a Construtivist perspective in the in the National Curricular Parameters for the Mathematics and also in the collection Matemática para Todos , also preserving sufficiently the Almost-empiric model